Knowledge of the early marriage in high school adolescents - Hamidah Hamidah; Tanaya Gita Kirani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Early marriage is prevalent among teenagers in Indonesia, leading to school dropouts, increased abortion rates, and higher maternal mortality rate (MMR) and infant mortality rate (IMR). This study aims to assess the knowledge of the early marriage in high school adolescents. This research is a descriptive quantitative study involving a sample of 151 students selected through stratified random sampling. Data was collected using a structured questionnaire and analyzed using bivariate analysis with chi-square test. The study found that more than half of the adolescents (59.6%) have inadequate knowledge about early marriage. Despite this, there was no statistically significant relationship between gender, age, maternal education, or parental income and adolescents knowledge about early marriage (p>0.05). The findings indicate that adolescents have insufficient knowledge about early marriage. This highlights the need for schools to provide targeted education on early marriage. Future research should explore factors contributing to early marriage incidences and evaluate the effectiveness of educational interventions.